2017
DOI: 10.1111/cas.13393
|View full text |Cite
|
Sign up to set email alerts
|

Review of the biologic and clinical significance of genetic mutations in angioimmunoblastic T‐cell lymphoma

Abstract: Angioimmunoblastic T‐cell lymphoma (AITL) is an age‐related malignant lymphoma, characterized by immune system‐dysregulated symptoms. Recent sequencing studies have clarified the recurrent mutations in ras homology family member A (RHOA) and in genes encoding epigenetic regulators, tet methyl cytosine dioxygenase 2 (TET2), DNA methyl transferase 3 alpha (DNMT3A) and isocitrate dehydrogenase 2, mitochondrial (IDH2), as well as those related to the T‐cell receptor signaling pathway in AITL. In this review, we fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 60 publications
0
25
0
Order By: Relevance
“…Mutations in AIFM-1 are related to fatal encephalomyopathy in infants ( 149 ). Recurrent mutations in IDH2 are associated with angioimmunoblastic T cell lymphoma ( 150 ). Polymorphisms in MnSOD can lead to abortion during the first trimester of pregnancy ( 151 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in AIFM-1 are related to fatal encephalomyopathy in infants ( 149 ). Recurrent mutations in IDH2 are associated with angioimmunoblastic T cell lymphoma ( 150 ). Polymorphisms in MnSOD can lead to abortion during the first trimester of pregnancy ( 151 ).…”
Section: Discussionmentioning
confidence: 99%
“…DNMT3A is an enzyme that catalyzes the transfer of a methyl group on cytosine residues in the CpG dinucleotide leading to repression of target gene expression. In AITL patients, inactivating mutations in DNMT3A were identified in 20-30% of the cases 69,70 . A hotspot mutation (p.R882H) in DNMT3A accounts for 15% of the DNMT3A mutations in AITL.…”
Section: Dmt3a Mutations In Aitlmentioning
confidence: 99%
“…AITL is more common in elderly patients attributed to the age-related premalignant mutations. 12 To date, the largest study recruited 1207 AITL patients confirmed that age > 60 years, progressive stage, and male were adverse factors of prognosis. 13 Somatic mutations were detected in 95% of individuals aged between 50 and 60 years old.…”
Section: Discussionmentioning
confidence: 98%